Is Transformational Leadership Suitable for Future Organizational Needs? - Masduki Asbari (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2020)
Do we need a new type of leadership to face the Fourth Industrial Revolution (4IR)? It’s Gallo & Hlupic (2019) question. According to them, the new model needed is a humanist, humane, humane leadership model. This model is considered a leadership model that not only has a radar that serves to understand what is happening throughout the organization but also a moral compass to direct the organization in the right direction, guided by ethical choices and responsibilities. Not just change, but a true shift towards human leadership, where trust and respect permeate the organization. This study seeks to answer these questions and at the same time propose a transformational leadership model as an answer to the needs of organizations facing 4IR